Causes, clinical assessment and management of paediatric bloody diarrhoea - Alshaikh, Attia Abdrabalnabi; Alshehri, Saeed Mohammad; Alsubaihi, Ibrahim Abdu; Boeisa, Mohammad Ahmed; Kiki, Bassam Khalid; Asiri, Ahmed Ali; Asiri, Ahmed Maddi; Aloufi, Shahad Ali; Azhari, Ayat Mohammad; Saklou, Afraa Faisal; Mansoor, Batool Abed (International Journal Of Community Medicine And Public Health, 2022)
Despite being easily preventable and treatable, diarrhoea continues to be a serious public health problem in impoverished and emerging countries. It is a typical sign of gastrointestinal issues brought on by numerous pathogens, including bacteria, viruses, and protozoa. Particularly in developing nations it is of great concern as it is associated with considerable mortality and morbidity in children. Despite the decline in mortality rate, it is still the second leading cause of mortality among children under five years of age. Bloody diarrhoea is characterized by intestinal inflammation, particularly of the colon, stomach pain, and severe diarrhoea with blood or mucus in the faeces. It is also referred as dysentery. Among the bacteria and parasites that cause dysentery include Entamoeba histolytica, Shigella, Campylobacter, Salmonella, Schistosoma mansoni, and Campylobacter. The most common cause of this disease is Shigella. The purpose of this research is to review the available information about causes, clinical assessment and management of paediatric bloody diarrhoea. Stool culture is a standard diagnostic measure. Digestive issues and nutritional inadequacies are more frequent in children with bloody diarrhoea. Bloody diarrhoea often lasts longer and is more problematic than watery diarrhoea. It has a high percentage of case fatalities and adversely impacts a child’s growth. Rehydration therapy shall be started immediately to prevent dehydration associated complications and fatalities. Treatment with fluoroquinolones as first-line medications, beta-lactams and cephalosporins as second-line medications is recommended. Further clinical research is however needed to define the clinical efficacy of available treatment and management strategies.